Representing quasi-homogenous materials - Tong, Xin; Wang, Jiaping; Lin, Steve; Guo, Baining; Shum, Harry (2005)
Representing quasi-homogenous materials is described. In one aspect, quasi-homogenous materials are modeled to generate a material model of a physical sample. The material model identifies how light is scattered by the quasi-homogenous materials. The material model, independent of an object model of the physical sample, provides information that is useful to texture surfaces of arbitrary types and sizes of mesh models (e.g., representing the physical sample or other objects) with the quasi-homogenous materials.
US Patent 7312797 B2